A Novel Reverse Phase High-Performance Liquid Chromatography Method Development and Validation for Determination and Estimation of Niraparib and Abiraterone Drug with its Bulk Form and Tablet Formulation - Roopa Redamala, (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: Measurement which is simultaneous of Niraparib and Abiraterone in/to bulk and pharmaceutical dosage form with forced degradation investigations, a straightforward, stability-indicating, and reliable reverse liquid reverse phase high-performance liquid chromatography approach has been devised and validated. Materials and Methods: The Sunfire C18 Column, measuring 100Å, 5 μm, 3 mm, and 250 mm, was employed as the stationary liquid for the separation. The mobile phase consisted of CH3OH and 0.1% trifluoroacetic acid in a 60:40 ratio, maintained at a flow velocity of 0.9 mL/min, with a maximum wavelength of 220 nm at a temp of 30°C. Niraparib and Abiraterone were shown to have average retention durations of 4.378 and 3.350 min, respectively. Results: Six injections of the Standard were used to study the system suitability characteristics, and the findings fell considerably below the accepted table threshold (limit of <2). A sequentiality analysis was conducted at 25–150% levels, and the R2 value was 0.999. Numerous validation measures, including robustness, precision, accuracy, limit of quantification,and limit of detection, were determined to be within the accepted table ranges. For Niraparib and Abiraterone, the recovery percentages were 100.29% and 100.13%, respectively. Conclusion: This method found very simple, accurately, responsive, fast, and cheap with a runtime within 8 min. Practically this method can be applied for the determination of assay in Tablet formulation as well.